Idiopathic Pulmonary Hemosiderosis in a Child with Recurrent Macrophage Activation Syndrome Secondary to Systemic Juvenile Idiopathic Arthritis - Kenan Barut; Sezgin Sahin; Amra Adrovic; Velat Sen; Ozgur Kasapcopur (Case Reports in Pediatrics)
Macrophage activation syndrome, a severe complication of systemic juvenile idiopathic arthritis and other inflammatory diseases, represents one of the most important rheumatological emergencies. Delayed diagnosis could lead to life-threatening complications. Pulmonary hemosiderosis has been classically characterized by a triad of anemia, hemoptysis, and lung infiltrates on chest radiogram. Although the majority of patients of pulmonary hemosiderosis are considered idiopathic, secondary hemosiderosis associated with known diseases could be seen. In this case report, we aimed to present gradually increased pulmonary manifestations due to pulmonary hemosiderosis with recurrent macrophage activation syndrome attacks in a child with systemic juvenile idiopathic arthritis.